POLITICAL SCIENCE: A CHANGING YISUIPLINE - نجيب د. ريمون; اسماعیل د. عبدالفتاح; شمبش د. علي (Dirasat in Economics and Business, 2022)
Political science in the twentieth century has shown a marked development not uncommon to the other areas of the sciences The first part of the article discuss political science as a discipline in the four classical stages: the philosophical, the legal, the realist, and the behavioral schools of political science and their individual and joint contributions to the discipline. The second part of the artical discusses the inter-relation. ship of political science with other areas of study and specifically with philosophy, morality and religion, law, economics, society, geography, history and psychology . sociology. It points out that while one or more of these could be of some help in political study and analysis, political phenomena have been known to develop and progress independently of any of other areas of knowledge. Nevertheless, these have contributed in the past and still contribute appreciably to the study of political science. The third part of the article discusses changes in the methodologies used in studying political science, how the changes came about as a result in emphasis, the changes in the schools of political thought, and the development in available research techniques. The authors discuss the contributions and shortcomings of each of the following methodological approaches : the philosophical the legalistic, the historical, and finally, the true scientific approach which has raised political science to a social science.